Enhancing learning and teaching quality: Intranet hierarchy optimisation and application of stereochemical molecular representations - Sosabowski, Michael H.; Aljawhiri, Steve; Herson, Katie; Olivier, George W.J. (Information services & use, 2000)
This article deals with the ongoing use and development of Intranet-based technologies within the School of Pharmacy and Biomolecular Sciences, University of Brighton. The course used as a test model is the M.Pharm. degree, a 4-year course with approximately 120 students per level. The student subjects of this study are the then Level 2 students. In this article we examine the continued optimisation of a School Intranet learning resource with regard to optimisation of the hierarchical structure. In response to a requirement previously identified, this work then focuses on the use of manipulatable molecular representations to enhance the learning and teaching of stereochemistry.